1995
DOI: 10.1063/1.113324
|View full text |Cite
|
Sign up to set email alerts
|

Photocurrent polarization in long-range ordered Ga0.5In0.5P

Abstract: Photocurrent polarization properties near the band gap of long-range ordered Ga0.5In0.5P have been investigated. The linearly polarized PC spectra of the ordered Ga0.5In0.5P show an absorption anisotropy for the [110] and [11̄0] directions together with a large band-gap reduction. The anistotropy in the PC spectra is due to a crystal-field splitting at the valence-band maximum in ordered Ga0.5In0.5P. The PC edge of the [110] polarization is lower at about 10 meV than one of the [11̄0]. The polarization spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 9 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…1 In particular, the electronic band structures in long-range ordered ͑Al x Ga 1Ϫx ͒ y In 1Ϫy P alloys have been investigated by optical measurements and theoretical calculations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] CuPt-type long-range ordering appears in ͑Al x Ga 1Ϫx ͒ y In 1Ϫy P alloys grown on GaAs͑001͒ substrates by metalorganic vapor-phase epitaxy ͑MOVPE͒. The ordered structure is equivalent to a monolayer superlattice alternating ͑Al x Ga 1Ϫx ͒and In-rich atomic planes along the ͓111͔ or ͓111͔ direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In particular, the electronic band structures in long-range ordered ͑Al x Ga 1Ϫx ͒ y In 1Ϫy P alloys have been investigated by optical measurements and theoretical calculations. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] CuPt-type long-range ordering appears in ͑Al x Ga 1Ϫx ͒ y In 1Ϫy P alloys grown on GaAs͑001͒ substrates by metalorganic vapor-phase epitaxy ͑MOVPE͒. The ordered structure is equivalent to a monolayer superlattice alternating ͑Al x Ga 1Ϫx ͒and In-rich atomic planes along the ͓111͔ or ͓111͔ direction.…”
Section: Introductionmentioning
confidence: 99%
“…The energy of the ⌫(L) band in ordered ͑Al x Ga 1Ϫx ͒ 0.5 In 0.5 P alloys with xϽ0.6 is higher than that of the ⌫ band. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] By utilizing the BGR in ordered alloys, we can produce a new direct gap ͑Al x Ga 1Ϫx ͒ 0.5 In 0.5 P, when the energy of the reduced ⌫ band crosses the X band. 19 On the other hand, it is well known that epitaxially grown ordered alloys are comprised of many domains with varying values of the order parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The new electronic band lineup shows a change of the band gap and a crystalfield splitting. [1][2][3][4][5][6][7][8][9] These properties can be continuously varied by controlling the long-range order parameter, which opens a new field of band-structure engineering. On the other hand, there has been a strong interest in indirect-gap semiconductors for their application to light emitting devices.…”
Section: Introductionmentioning
confidence: 99%
“…The degree of long-range ordering in ͑Al x Ga 1Ϫx ) y In 1Ϫy P can be controlled by the growth conditions, such as growth temperature, the gas-flow ratio of column-V and -III sources, and substrate orientation. [1][2][3][4][5][6][7][8][9][17][18][19][20][21][22][23][24][25] The doubling periodicity along the ͓111͔ or ͓111͔ direction causes a band folding of the L point to the ⌫ point. Here, the folded L band is labeled as ⌫͑L͒.…”
Section: Introductionmentioning
confidence: 99%
“…Spontaneous ordering in III-V semiconductors, GaInP 2 for instance, brings about changes in their band structures from that of the corresponding disordered alloys [1], and causes changes in the polarization of their optical spectra [2].. Optical anisotropy caused by Cu-Pt ordering has been observed in various spectroscopic studies: photoluminescence (PL) and PL excitation [3], piezomodulated reflectance [4], reflectance difference [5], electroreflectance [6] and photocurrent [7]. Qualitatively, these studies have all shown the change in crystal symmetry as a result of ordering.…”
Section: Introductionmentioning
confidence: 99%